Ответы и объяснения

2013-01-07T19:13:23+04:00

-120Х^2+34Х-1=0 умножаем все на -1

120х^2-34Х+1=0

D=(-34)^2-4*120*1=1156-480=676

D=26

 Х1=34-26/2*120=8/240=1/30

х2=34+26/2*120=60/240=1/4 

2013-01-07T19:16:12+04:00

Вроде через дискриминант!

-120х^2+34х-1=0

D=1156-4*(-120)*(-1)=676

Х1=-34+26        -8          1

                            -----= --------

 

       ----------- = -240         -30

             -240

 

 

Х2= -34-26      -60            1

       ------------ = ------  = ------

           -240       -240         4